Effects of lactobacillus and serratopeptidase supplementation on growth performance, hematology, immune response, and intestinal morphology in broiler chicks - Muhammad Mushtaq; Hanan Al-Khalaifah; Qurat ul-Ain; Imran Ullah; Muqadar shah; Ibrahim A. Alhidary; Shabana Naz; Rifat Ullah Khan; Ala Abudabos (Poultry Science, 2025)
This study evaluated the effects of different levels of Lactobacillus and serratopeptidase enzyme supplementation on growth performance, immune response, hematological parameters, and intestinal histomorphology in broiler chicks. A total of 320-day-old male Hubbard broilers were assigned to four dietary treatments (five replicates) in a completely randomized design as follow: a control diet, and diets supplemented with Lactobacillus at 2 × 10¹°CFU/kg, 3 × 10¹°CFU/kg, and 4 × 10¹°CFU/kg, each combined with 5 mg/kg serratopeptidase. Feed intake, weight gain, and feed conversion ratio (FCR) were monitored weekly. Blood samples were analyzed for hematological and immunological parameters, while intestinal histology was assessed. Results indicated that feed intake was significantly reduced in the highest supplementation (LSE3) group (P < 0.0001), while weight gain and FCR improved significantly compared to the control (P < 0.0001). Although antibody titers against Newcastle Disease and Infectious Bronchitis increased, differences were not statistically significant. Histomorphometric analysis revealed significantly longer villus height and decrease in crypt depth (P = 0.001) in LSE3. Overall, Lactobacillus and serratopeptidase supplementation (LSE3) improved growth performance and intestinal morphology, with the highest inclusion level yielding the best results, suggesting potential benefits for broiler production efficiency.